Effect of tissue flossing on eccentric exercise-induced muscle damage: A randomized controlled trial - Chen, Jianxin; Cheng, Fang; Yang, Jinqi; Yang, Jinfeng; Ran, Jianxin; Liao, Yuanpeng (Biology of Sport, 2025)
Tissue flossing (TF) is a novel technique designed to improve muscle and joint function and performance. This study investigated the effects of TF on exercise-induced muscle damage (EIMD) in 24 males randomized into TF ( n = 12) or control (CON, n = 12) groups. Participants performed dominant thigh quadriceps isokinetic eccentric exercises to induce EIMD, 10 sets × 12 repetitions. The TF group performed TF interventions (active movement during floss band wrapping, three times a session) immediately after and 24–48 h postexercise. Creatine kinase (CK), knee extensor eccentric strength, pressure pain threshold (PPT), and deep fascia sliding (DFS) of quadriceps were measured at baseline and 24, 48, and 72 h postexercise. CK levels significantly increased over time postexercise, with CON showing a greater increase than TF (all p < 0.05). Knee extensor eccentric strength returned to baseline levels for TF at 48 h (= 0.081) and CON at 72 h (= 0.058), with TF showing greater improvement postexercise (all p < 0.05). Both groups’ rectus femoris PPT returned to baseline at 72 h (TF, = 0.303; CON, = 0.272). However, only TF returned to baseline in the vastus medialis PPT and DFS at 72 h and the vastus lateralis DFS at 48 h (all p > 0.05). Furthermore, the PPT and DFS of the vastus medialis and lateralis were significantly greater in TF than in CON over time postexercise (all p < 0.05). Overall, TF is an effective strategy for alleviating EIMD after high-intensity exercise.